What's on the Menu? - Haley, Andrew P. (Journal of American History, 2015)
A review of the website "What's on the Menu?," featuring digitized images of nineteenth- and twentieth-century menus, created and maintained by the NYPL Labs of the New York Public Library in New York City, and available at http://menus.nypl.org/, is presented.